NATURAL SPECIATION OF MN, NI, AND ZN AT THE MICROMETER SCALE IN A CLAYEY PADDY SOIL USING X-RAY FLUORESCENCE, ABSORPTION, AND DIFFRACTION - Manceau A.; Tommaseo C.; Geoffroy N.; Tisserand D.; Rihs S.; Chateigner D.; Schlegel M.; Marcus M.A.; Tamura N.; Chen Z.-S. (My University, 2005)
The natural speciation of Mn (0.19 g/kg), Ni (46 mg/kg), and Zn (42 mg/kg) in the argillic horizon (120 cm depth, pH = 5.6) of an Ultisol from a paddy soil in northern Taiwan was investigated by advanced X-ray synchrotron techniques. Microchemical associations were imaged by synchrotron-based X-ray microfluorescence, host minerals were identified by standard and micrometer-resolved X-ray diffraction, and the local coordination environment of Mn, Ni, and Zn was probed using extended X-ray absorption fine structure (EXAFS) spectroscopy on a powdered sample and a soil thin section, and polarized EXAFS spectroscopy on a highly textured self-supporting clay film from the <2 μm fraction of the soil. Manganese was concentrated in Fe-Mn soft mottles (44.4 g/kg) as turbostratic hexagonal birnessite and lithiophorite having Mn3+/Mn4+ atomic ratios of ∼20% and 50%, respectively. Quantitative analysis of high-order scattering paths of the EXAFS spectrum for natural and synthetic lithiophorite revealed that Mn3+ and Mn4+ are ordered in the layer. A structural model is proposed, in which Mn4+ and Mn3+ are ordered similarly to Al and Li in the layer, with Mn3+ cations being surrounded by six Mn4+, and Mn4+ cations by three Mn3+ and three Mn4+. Similar cation ordering in the manganese and aluminum layers likely provides a more homogeneous local balance of the excess and deficit of charges in each layer and increases the stability of lithiophorite. Ni (r = 0.70 Å) substitutes for Mn (r(Mn4+) = 0.54 Å, r(Mn3+) = 0.65 Å) in the manganese layer in the natural lithiophorite. In contrast, Zn (r = 0.74 Å) fills vacant sites in the gibbsitic layer of natural lithiophorite, in a similar manner as lithium (r = 0.74 Å) in synthetic lithiophorite. The partitioning of Ni and Zn between the two layers is a result of the general preference of Ni, whose size is intermediate between those of Mn3+ and Li+, for slightly smaller sites. In contrast with nickel, which is detected only where there is lithiophorite, the Zn-lithiophorite association found in Fe-Mn mottles is not representative of the bulk soil. The combined use of X-ray diffraction, and powder and polarized EXAFS spectroscopy revealed that Zn is predominantly bound to hydroxy-Al interlayers sandwiched between 2:1 vermiculite layers in the fine soil matrix. The incorporation of Zn in the gibbsitic layer of both lithiophorite and vermiculite helps increase the stability of these minerals by providing positive charge to balance the negative charge from the 2:1 phyllosilicate layer and the layer of lithiophorite. This binding environment for zinc is probably the main mechanism by which zinc is sequestered in acidic to near-neutral aluminum-rich clayey soils.